Efeito da limpeza pós-condicionamento e do tratamento térmico do silano na resistência de união de um cimento resinoso à cerâmica - Hipólito, Ana Carolina [UNESP] (2014)
Purpose: The aim of this study was to evaluate the effect of cleaning with phosphoric acid after etching of ceramic and heat treatment of the silane with a stream of hot air on the bond strength of a resin cemente to lithium dissiliacte ceramic submitted to aging. Method: Sixty-‐four blocks-‐ceramic lithium silicate (IPS e-‐max CAD, Ivoclar Vivadent) and composite resin were fabricated (7x8x4mm). The specimens were randomly divided into 4 groups (n = 16) that received the following treatments: HFS (control group): 10% hydrofluoric acid and silane; HFPS: hydrofluoric acid, 37% phosphoric acid and silane; HFSA: hydrofluoric acid and silane heated (45 ◦ C ± 5 ◦ C); HFPSa: hydrofluoric acid, phosphoric acid and heated silane. The specimens were cemented with a dual resin cement, later the specimens were divided into two aging conditions (n = 8): N -‐ no aging and TC: thermocycling, 12,000 x 5◦C -‐ 55◦C. They were submitted to microtensile test in a testing machine with a speed of 0.7 mm / min. Fractured surfaces were examined to determine the failure mode. Statistical data were analyzed by ANOVA with 2 factors and the averages compared by Tukey test (p <0,05). Results: The group HFSa aged showed the highest bond strength (21.49 ± 2.29 MPa), however, without statistical difference for the control group. There was no statistically significant difference between aged and non-‐aged samples, except for, a statistically significant difference in the HFSA group (p <0.05). Significance: The heat treatment of the silane and cleaning after etching with phosphoric acid did not increase the bond strength of ceramic resin